METODE KRITIK SANAD DAN MATAN HADIS - Rahmiah Nur R; Mirna Yunita; Muhammad Ali (AL-BAYAN INSTITUTE, 2025)
Sanad and matn criticism are two fundamental pillars in the science of hadith, playing a crucial role in determining the validity and authenticity of a narration. Sanad criticism focuses on evaluating the integrity and reliability of the chain of narrators, including their moral uprightness (‘adalah), precision (ḍabt), and the continuity of the chain. On the other hand, matn criticism examines the content of the hadith, assessing its consistency with the Qur’an, rationality, historical facts, and the absence of linguistic irregularities or contradictions. This study aims to analyze the methodologies and principles applied in sanad and matn criticism, as well as their implications for the classification of hadith into sahih, hasan, and da‘if. Through a literature review of classical scholars such as al-Bukhari, Muslim, and Ibn Hajar al-Asqalani, as well as contemporary scholars, it is concluded that a strict and systematic approach to hadith criticism serves as a cornerstone for preserving the authenticity of Islamic teachings derived from the Prophet’s traditions. This paper emphasizes the necessity of integrating both sanad and matn criticism to prevent deviations in religious understanding and practice.